Chapter 4 Reversion and reprisal The allure of going back and the negotiation of historical identities - Daugbjerg, Mads (Taylor & Francis, 2019)
As noted by Pierre Nora (1989, p. 17), 'no-one knows what the past will be made of next'. While this is indeed so, it is also the case that the past will surely be 'made' somehow. In this chapter, we take a look at those makings and the ubiquitous desire to recreate what once was that arguably undergirds almost any heritage practice.